The Role of Public Relations and the Positive Image of Regional Owned Enterprises (BUMD) - Sofiani, Anantri Putri; Anjani, Lulu Millati; Fatmawati, Nizhaamul; Nurfalah, Farida (Syntax Literate, 2024)
Public relations is a party that can connect a company with the community to create reciprocal communication and establish good relationships. This research aims to determine how BUMDs carry out their public relations role and create a positive image for the company. This research uses a qualitative descriptive analysis method. Interviews, observation, and documentation were carried out using data collection methods. The theory used in this research is the Role Theory of Public Relations. The research results show that the role of Regional Drinking Water Company (PDAM) Tirtajati Public Relations is to provide comfort, understanding, information, and solutions to customers. Public Relations of PDAM Tirtajati collects aspirations and complaints and then connects them to related fields. Several inhibiting factors, such as insufficient services, impacted the community's negative response. Public Relations of PDAM Tirtajati strives to provide excellent service, establishes good communication with customers, provides complaint services via WhatsApp Center and Social Media to make it easier for the public, and establishes external communication with other agencies or organizations, public relations also provide explanation of the problems that occur, then offers solutions and treatments to resolve issues.